Using Bibliometric Analysis to Identify the Intellectual Structure, Emerging Trends and Future Research Opportunities in Virtual Reality and Dementia - Sobral, M.; Pestana, M.H.; Filipe, J.; luizammoutinho@gmail.com (29Th Euroasia Business and Economics Society ( EBES) Conference_-10-12 October ISCTE-IUL, 2019)
Purpose: This paper applies the CiteSpace bibliometric visualisation method to identify patterns, trends and future research opportunities in virtual reality (VR) and dementia. Methods: Data was collected between from 1998-2018, from the Web-of-Science (WoS) and Scopus databases to build an expanded network encompassing 355 documents, 203 articles, 252 sources of publication, 189 journals, 537 keywords, and 19,238 citations. Results: The results show differences between WoS and Scopus in terms of scope, the volume of data, and coverage policies. For each new publication and citation in WoS there is a 0.997 publication, and 10.3 citations in Scopus. Scopus has a lower number of co-authors per document, articles, journals, and papers involving international collaboration, yet it covers more sources, documents, and has a higher productivity rate. Both datasets complement each other. Neuroscience is the main area, the Journal of Alzheimer’s Disease is the top source, Riva G. is the most productive author, the USA is the top country in terms of international collaboration, and the UK emerged as the leading contributor. The maturity of research in this field is remarkable because, while focused primarily on Alzheimers’s disease, memory and cognitive rehabilitation, it shows a dynamic shift in its importance over time, and some new topics are now catching the attention of researchers. Conclusions: The co-citation and co-authorship network analysis evidences an increasing interest in VR and dementia research and can be used to guide researchers and practitioners in learning where this field comes from, stands now and ought to go in the future.